Предмет: Математика,
автор: Great9999
(-2x+9)×(-x+3)=0 решите уравнение
Ответы
Автор ответа:
0
(-2x+9)*(-x+3)=0
-2x^2-6x+9x+27=0
-2x^2+3x+27=0 / * -1
2x^2-3x-27=0
Д=9+4*2*27=9+216=225
x1.2=3+-5/4 x1=2 x2=-1/2
-2x^2-6x+9x+27=0
-2x^2+3x+27=0 / * -1
2x^2-3x-27=0
Д=9+4*2*27=9+216=225
x1.2=3+-5/4 x1=2 x2=-1/2
Похожие вопросы
Предмет: Русский язык,
автор: nadyakotenok5
Предмет: Музыка,
автор: timurkrasavec2000
Предмет: Английский язык,
автор: fallsx9898
Предмет: Геометрия,
автор: Nasti12
Предмет: Литература,
автор: horoshstca